Makna Horas dalam Konteks Agama Katolik: Studi tentang Relevansi dan Aplikasi dalam Kehidupan Sehari-hari - Ona Sastri Lumban Tobing; Oktavianey G. P. H. Meman (Borneo Review, 2025)
This study examines the meaning and function of the greeting Horas within the context of Batak Toba Catholic communities, focusing on its relevance and application to Catholic faith values in daily life. As a traditional Batak salutation, Horasserves not only as a medium of social communication but also represents theological and cultural dimensions embodying concepts of salvation, harmony, and well-being from a Catholic perspective. Employing a descriptive-qualitative method, data were collected through in-depth interviews, participatory observation, and literature review of cultural texts and relevant Catholic Church documents. The findings show that the philosophical meaning of Horas is coherently linked to Catholic teachings regarding love, peace, and hope for eternal life, functioning as a medium for faith inculturation within Batak culture. The practice of Horas among Batak Catholics exemplifies harmonious integration between local cultural values and Christian spirituality, shaping a strong religious identity amid cultural plurality. This study affirms the importance of inculturative approaches in understanding faith expressions and encourages the preservation of local noble values in the development of religious life that is contextual and relevant for contemporary Indonesian society.